2013
DOI: 10.18475/cjos.v47i1.a8
|View full text |Cite
|
Sign up to set email alerts
|

The Yellow Stingray,Urobatis jamaicensis(Chondrichthyes: Urotrygonidae): a synoptic review

Abstract: The yellow stingray, Urobatis jamaicensis (Cuvier) has been the subject of a multitude of diverse studies on its natural history, morphology, and physiology. We have attempted here to briefly review all the studies on U. jamaicensis both published and unpublished with the goal of providing comparative information for researchers working on related species as well as to highlight areas of research requiring further investigation in this one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
1
10
1
1
Order By: Relevance
“…The present study was however, unable to assess this trend properly due to an abundance of individuals within 160-200 mm W D with few individuals smaller or larger and only a third of the sample size representing immature individuals. In addition, the recorded average W D for U. jamaicensis in Florida is 160 mm (Spieler et al, 2013) whereas the present average W D was 181 mm, suggesting that a larger sample of smaller individuals may be necessary to describe ontogenetic diet shifts in this species.…”
Section: I E Tcontrasting
confidence: 73%
See 1 more Smart Citation
“…The present study was however, unable to assess this trend properly due to an abundance of individuals within 160-200 mm W D with few individuals smaller or larger and only a third of the sample size representing immature individuals. In addition, the recorded average W D for U. jamaicensis in Florida is 160 mm (Spieler et al, 2013) whereas the present average W D was 181 mm, suggesting that a larger sample of smaller individuals may be necessary to describe ontogenetic diet shifts in this species.…”
Section: I E Tcontrasting
confidence: 73%
“…All infauna was recorded in high abundance with the exception of the two most common groups found in the dietary content of U. jamaicensis , annelids and crustaceans, which were recorded at very low levels (crustaceans n = 7, 0·13% of total, annelids n = 47, 0·89%). While previous studies have suggested a generalist feeding strategy in U. jamaicensis (Yanez‐Arancibia & Amezcua‐Linares, ; Spieler et al, ), both foraging strategy plots and Manly‐Chesson analysis revealed clear specialization on annelids in U. jamaicensis . In addition, the difference between infauna sampled in the environment and prey items found within the stomach contents may indicate that U. jamaicensis are feeding in separate habitats, secondary to where they were captured and sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a number of long‐term coral research and monitoring surveys have been underway in the area [Gilliam et al, ; Kilfoyle et al, ] as well as cable benthic impact assessments for the SFOMF [Messing et al, ]. There is rich literature on the geology and biology associated with the SFOMF and the surrounding area, and an abundant and diverse marine community including teleost fish, elasmobranchs, and turtles has been documented [Baron et al, ; Banks et al, ; Bryan et al, ; Spieler et al, ; Gilliam et al, ; Kilfoyle et al, ]. Marine fish, 289 species, have been documented from a baseline study of reef fish in southeast Florida [Kilfoyle et al, ], and a compiled total of 354 coral reef and coastal fish species have been recorded in Broward County from multiple studies over the course of the past 20+ years, including multiple electric‐sensitive species such as sharks and rays that are residents in the area and/or migrate through on the way to or from breeding sites [Schwartz, ; Castro, ; Kohler et al, ; Kohler and Turner, ].…”
Section: Methodsmentioning
confidence: 99%
“…Marine fish, 289 species, have been documented from a baseline study of reef fish in southeast Florida [Kilfoyle et al, ], and a compiled total of 354 coral reef and coastal fish species have been recorded in Broward County from multiple studies over the course of the past 20+ years, including multiple electric‐sensitive species such as sharks and rays that are residents in the area and/or migrate through on the way to or from breeding sites [Schwartz, ; Castro, ; Kohler et al, ; Kohler and Turner, ]. For example, the Yellow Stingray ( Urobatis jamaicensis ) is very abundant in the area, with a home range that includes the sand, hardbottom, and coral reef habitats within the SFOMF [Fahy et al, ; Spieler et al, ], and Blacktip Sharks ( Carcharhinus limbatus ) make annual seasonal migrations through the area [Kaijura and Tellman, ].…”
Section: Methodsmentioning
confidence: 99%
“…Survival in elasmobranchs is generally unaffected by exposure to high CO 2 (Di Santo, 2015; Rosa et al ., 2017); however, the mediation of key metabolic functions with direct relevance to survival has scarcely been investigated. Here, we examine the effects of exposure to very high CO 2 (pH = 6.8, p CO 2 = ~13,000 μatm) on wound healing in a well‐studied elasmobranch (Spieler et al ., 2013), the yellow ray Urobatis jamaicensis (Cuvier 1816), to test the hypothesis that healing slows under high CO 2 exposure. As somatic growth can be reduced in fishes exposed to high CO 2 (Ishimatsu et al ., 2008), we predicted that tissue regeneration during healing would also be affected.…”
Section: Parameter Haematocrit Wound Diameter Body Mass Mean Effect Smentioning
confidence: 99%